Annual Plan 1993-94 Statements - Planning Commission (Planning Commission, 1992)
Progress of Expenditure during the Annual Plans 1991-92 and 1992-93 and proposed outlay for the Annual Plan 1993-94 Physical Targets and Achievements during the Annual Plans 1991-92 and1992- 93 and Proposals for the Annual Plan 1993- 94 Proposals for Spillover and Ongoing Programmes/Projects Proposals for Maximizing Benefits of Completed Programmes/Projects(As on 31.3.1993) Proposals for Programmes/Projects -- New Schemes of Eighth Plan Summary Statement - Proposals for Programmes/Projects Statement Regarding Externally Aided Projects Annual Plan 1993-94:Outlays - By Heads of Development(For District Plan) Centrally Sponsored Schemes Tribal Sub-Plan(TSP-I)Financial Outlays: Proposals for TSP 1993-94.
Planning Department